2010
DOI: 10.3233/jad-2010-1257
|View full text |Cite
|
Sign up to set email alerts
|

Increased Pro-Inflammatory Response by Dendritic Cells from Patients with Alzheimer's Disease

Abstract: Abstract. Alzheimer's disease (AD) is characterized by abnormal accumulation of amyloid-β peptide (Aβ) into extracellular fibrillar deposits, paralleled by chronic neuroinflammatory processes. Although Aβ seems to be causative in AD brain damage, the role of the immune system and its mechanisms still remain to be clarified. We have recently shown that normal monocyte-derived dendritic cells (MDDCs), when differentiated in the presence of Aβ1−42, acquire an inflammatory phenotype and a reduced antigen presentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 40 publications
4
31
0
Order By: Relevance
“…Myeloid cells from memory-impaired individuals also have a greater stimulus-induced proinflammatory response [91], which mirrors animal studies demonstrating the same effect in bone marrow-derived macrophages from APP/PS1 mice [98]. However, it has been found that DCs from AD patients have a reduced ability to stimulate T cell proliferation [94]. The innate immune system provides the first line of defense against infectious agents, thus an altered response here can have severe consequences for the individual and their ability to control, and respond to, infection.…”
Section: Reviewmentioning
confidence: 87%
See 1 more Smart Citation
“…Myeloid cells from memory-impaired individuals also have a greater stimulus-induced proinflammatory response [91], which mirrors animal studies demonstrating the same effect in bone marrow-derived macrophages from APP/PS1 mice [98]. However, it has been found that DCs from AD patients have a reduced ability to stimulate T cell proliferation [94]. The innate immune system provides the first line of defense against infectious agents, thus an altered response here can have severe consequences for the individual and their ability to control, and respond to, infection.…”
Section: Reviewmentioning
confidence: 87%
“…Indeed the population of circulating myeloid dendritic cells (DCs) is decreased in the elderly [92] and these cells are further reduced in AD [93]. AD patients had increased levels of ICAM-1 + monocyte-derived DCs [94] and increased expression of MHC class II and CD16 on CD14 + monocytes [95]. Saresella and colleagues also found a significant increase in IL-6- and IL-23-producing CD14 + monocyte/macrophages in AD patients, while IL-10 + cells were reduced [75].…”
Section: Reviewmentioning
confidence: 99%
“…Monocytes migrate across a compromised blood-brain barrier and express chemokine receptors to guide immune cells to inflammatory sites [9,10,34,35,36]. Monocytic cell adhesion molecules are altered in AD patients [33,37]. Further, the expression of chemokine receptors and cytokines was found to be increased in PBMCs of AD patients [38].…”
Section: Discussionmentioning
confidence: 99%
“…Within this scenario, where A or other AD-related stressor factors could induce the release of IL-18, likely via PRR triggering, it is conceivable that this cytokine would exacerbate the release by neighboring glial cells or peripheral immune cells, of diverse toxic inflammatory molecules, which may lead to a vicious cycle where inflammatory processes contribute to different aspects of AD neurodegeneration. In keeping with a potential contribute of peripheral immune cells in amplifying the AD inflammatory milieu, we recently demonstrated that myeloidderived DCs obtained from AD patients show an over activated inflammatory state and a reduced antigen presenting ability, as compared to cells of healthy control subjects [132]. Since in a previous in vitro study we have shown that A treatment is able to sustain inflammation by driving monocyte differentiation towards an IL-18 producing DC phenotype [133], it is probable that IL-18 would exacerbate a neuroinflammatory responses in a AD-specific and DCdependent fashion also in vivo conditions.…”
Section: Il-1f7/il-18bpmentioning
confidence: 97%